PERANCANGAN SISTEM INFORMASI PENDAFTARAN RAWAT JALAN BERBASIS WEB DI. RSAU DR.M. SALAMUN - D.yani; Johni S pasaribu; Irda sari (Universitas Widyatama, 2022)
Abstract- An outpatient medical record information system is a system that aims to manage the data of patients who are seeking treatment until the patient is discharged from the hospital or clinic.The information system designed is very important to prevent procedural errors in the implementation of registration and data management. The use of information technology, computers, and internet technology has penetrated into the world of health services, one of which is administrative orderly services, namely online or offline outpatient registration services carried out by officers. The design of this information system aims to design a new system or design to develop an electronic information program that aims to facilitate the implementation of integrated web-based outpatient registration so that it becomes one of the alternative systems that are of good quality and good. in accordance with the place of observation that the author made on September 25, 2019 at RSAU dr. M.salamun. designing the Application Program that the author made is a web-based outpatient registration application system using php framework software i.e. Laravel and phpMyadmin freeware that supports MySQL databse. The methodologies for developing this system are the UML Usecase Diagram method, and the Activity Diagram.